Le couloir ouest-saharien : un espace gradué - Claire Cécile Mitatre (L’Année du Maghreb)
Before the 70s, the Arab speaking people of Western Sahara never defined themselves as "Sahrawi" to differentiate themselves from their more or less distant neighbors. Indeed the term was created by militants in their effort to build a model of resistance against Spanish colonization and was endorsed in the struggle against the claims of Morocco's sovereignty over the territory. For the past twenty years, the Arab speaking people of the Oued Noun area, a region located on a territory not contested by Morocco, a hundred kilometers north of the geopolitical boundary of Western Sahara, have also referred to themselves as "Sahrawi" particularly to set themselves apart from their Berber neighbors. Yet, the use of this term with “quasi-ethnic connotations” by Arabic speakers of Moorish culture on Moroccan territory cannot be reduced to a strictly political issue. Focusing our study on how these Arabic speaking people position themselves, from a linguistic and cultural point of view, vis-à-vis their more or less distant neighbors, will help us understand the logic underlying the recent adoption of this ethnonym beyond the geopolitical borders of Western Sahara.